Implementasi Metode Resitasi dalam Meningkatkan Hasil Belajar Mapel Fiqih Siswa Kelas IV di MI Roudlotul Mubtadiin - Sulfatun Naimah; M. Anang Sholikudin; Wiwin Fachrudin Yusuf; Achmat Mubarok (LPPM STAI Ihyaul Ulum Gresik, 2023)
The recitation method was intended to be used in this investigation to help grade IV students at MI Roudlotul Mubtadiin learn more about fiqh. Research was conducted utilizing a qualitative methodology known as Classroom Action (PTK), The data needed for this study was acquired via watching student and teacher activities and looking at test results for learning evaluations. According to the findings, class IV MI Roudlotul Mubtadiin students' learning outcomes in fiqh courses might be improved by using the recitation approach. Students' test results from three cycles, namely the pre-cycle, demonstrate this. which had results with an average of 65.66 and a completion rate of 63%; the cycle I results, which had results with an average of 76.22 and a completion rate of 77%; and the cycle II results, which had results with an average of 87.11 and a completion rate of 96%.